Hydrological Parameter Analysis Based on Similarity Theory and 3S Technology. (January 2019) - Zheng, Shi; Tan, Hong-Xia; Chen, Huan-Bao; Hu, Lin-Lin
Abstract: Parameter identification is an important step on the hydrological modelling. Nevertheless, some parameters of the hydrological model cannot be determined directly through experimental observation, which are related to watershed characteristics. As a result, the way to analyze effectively the correlation between the parameters and watershed characteristics become the important content of hydrological model development. In this study, we use similarity theory combines with 3S technolog (RS, GIS and GPS) to analyze the hydrological model parameters. The results show that the distances on the parameters of two similar watersheds are mostly small and close in the geometric space. This founding can help us to find some of the laws of runoff response function.